(untitled) (Boletin Médico de Postgrado, 2022)
The objective of the research was to describe the emotional state of adolescents of the Los Angeles school located in the municipality of San Felipe, Yaracuy state, during the third phase of SARS-CoV-2 virus infection. The population consisted of a total of 42 adolescents with an average age of 13.8 years, 70% were females with an educational level of second year of high school. The Depression, Anxiety and Stress Scale (DASS-21) abbreviated version questionnaire was used to collect the information. Anxiety was the most frequent symptom in the severe classification followed by depression (moderate to severe) and stress (moderate). In conclusion, there was a profound alteration of the emotional state of the adolescents due to the quarantine that changed their daily routine. It is recommended that the DASS 21 scale be applied in educational institutions for the purpose of early detection of possible disorders of emotional state, especially in the adolescent population.